Association between coronary artery calcium score and stent expansion in percutaneous coronary intervention. (1st July 2021) - Komaki, Soichi; Ishii, Masanobu; Ikebe, Sou; Kaichi, Ryota; Mori, Takayuki; Marume, Kyohei; Kurogi, Kazumasa; Yamamoto, Nobuyasu
Abstract: Background: Measurement of the coronary artery calcification score using multidetector computed tomography (MDCT) is a useful noninvasive test for the diagnosis of coronary artery disease. However, whether pre-intervention assessment of the target vessel coronary artery calcification (TV-CAC) score is associated with stent expansion failure and future target lesion revascularization (TLR), remains unknown. This study aimed to determine the association between the TV-CAC score measured by MDCT and stent expansion rate in patients who underwent IVUS-guided PCI for stable angina. Methods: We conducted a retrospective observational study including 135 consecutive patients (186 target lesions) who underwent MDCT and were scheduled for the first PCI. The patients were divided into 2 groups based on the median value of the TV-CAC score. The primary outcome was the stent expansion rate measured by IVUS after stent implantation. The secondary outcome was TLR within 1 year. Results: Stent expansion rate was associated with the TV-CAC score (p < 0.001). According to the ROC curve analysis, the TV-CAC score had the largest area under the curve (AUC) for the stent expansion area of 0.90 (AUC = 0.893, p < 0.001). The TV-CAC score was a positive predictor for stent expansion rate of <90% (odds ratio: 7.54, p < 0.001). Mediation analysis showed that stent under-expansion was a mediator of the association between high TV-CAC and TLR. Conclusions: Our study demonstrates that pre-intervention assessment of TV-CAC using MDCT is a predictor of stent expansion. The TV-CAC score might predict the complexity and help in the PCI operative strategy. Highlights: The present study showed that high TV-CAC assessed using the multidetector computed tomography is a predictor of stent under-expansion. Stent under-expansion is a mediator of the association between high TV-CAC score and in-stent restenosis. Assessing the TV-CAC score before PCI might be clinically useful to reduce future TLR due to stent under-expansion.